Investigating Photochromic Behavior of Organic Dyes in Solution Form using Multilevel Factorial Design - Najiah Nadir; Zaharah Wahid; Amir Akramin Shafie; Farah B. Ahmad; Mat Tamizi Zainuddin (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Photochromic compounds, namely spiropyran, spirooxazine, and naphthopyran, have received much attention, because of their high potential applications in various industrial fields. The aim of this study is to understand the behavior of three photochromic dyes in solution form via statistical approach. The types of dyes and solvents were screened using multilevel factorial design. From the analysis of variance results, it was found that the types of dyes and solvents used as well as their interaction have significant effects on the absorbance and photostability. The naphthopyran compound displayed highest change in absorbance intensity, followed by spiropyran and spirooxazine, when dissolved in isopropanol separately. However, the spirooxazine is the most photostable dye compared to naphthopyran and spiropyran, with ethanol as the solvent. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).